An Analysis of the Application of Government Accounting Standards at the Central Statistics Agency in Medan City - Rischa Herlina Nadapdap; Vina Arnita (International Forum of Researchers and Lecturers, 2025)
This study examines the implementation of accrual-based Government Accounting Standards (SAP) at the Central Statistics Agency (BPS) of Medan City, in accordance with Government Regulation No. 71 of 2010. The research aims to evaluate financial management practices, SAP implementation, and the quality of financial reports. A qualitative approach was employed, with data collected through interviews, observation, and document analysis. The findings indicate that BPS Medan City has adopted accrual-based SAP by preparing financial reports, including the Budget Realization Report (LRA), Balance Sheet, Operational Report, and Notes to Financial Statements (CaLK). These reports meet qualitative characteristics such as relevance, reliability, comparability, and clarity. However, challenges include limited staff understanding of accrual principles and technical issues in transaction recording. The study concludes that SAP implementation has enhanced financial transparency and accountability, though improvements in human resource capacity and support systems are needed for more effective execution. However, challenges were identified in the implementation process. Limited staff understanding of accrual accounting principles has posed difficulties in proper transaction recording, especially in translating cash-based accounting systems to accrual-based systems. In addition, there are technical challenges related to the integration of financial software, which sometimes hampers the smooth generation of required financial reports. Despite these challenges, the study concludes that SAP implementation has enhanced financial transparency and accountability within BPS Medan City. The findings suggest that further improvements in human resource capacity, including training in accrual accounting principles, as well as strengthening technical support systems, are necessary for more effective execution. The study recommends that BPS Medan City focus on capacity building and system optimization to ensure the long-term success and sustainability of accrual-based accounting practices.